Using Both Classical and Chemometric Chromatographic Measurements to Quantify and Monitor the in‐vitro Dissolution Profiles of Lamivudine and Zidovudine in Combined Tablets. Issue 43 (16th November 2022) - Dinç, Erdal; Özdemir, Nurten; Tilkan, M. Günseli; Rouhani, Ghazal; Büker, Eda; Hoang, Vu Dang
Abstract: Classical and chemometric calibration strategies based‐Ultra Performance Liquid Chromatography‐Photodiode Array (UPLC‐PDA) measurements were improved to monitor the in‐vitro dissolution profiles of lamivudine (LAM) and zidovudine (ZID) in tablets and to quantify drugs. To generate UPLC‐PDA data, UPLC analysis was done using the mobile phase containing acetonitrile‐acetate buffer pH 5.0 (18 : 82, v/v). In the classical strategy, calibration curves were obtained by using the peak area ratios detected at 274 nm for LAM and 268 nm for ZID, respectively. Principal component regression (PCR) and partial least squares (PLS) strategies were used to solve the same problem using UPLC‐PDA measurements obtained at eight different wavelengths. Both classical and chemometric approaches were successfully applied for drugs assay and in‐vitro dissolution testing. Assay results showed that the proposed chemometric tools gave better results because they helped to minimize the effect of chromatographic issues that commonly occur with the classical UPLC approach, such as the higher standard deviation of the assay results. Abstract : In this work, classical and chemometric calibration strategies using UPLC‐PDA measurements with photodiode array detection were improved and validated to monitor the in‐vitro dissolution profiles of lamivudine (LAM) and zidovudine (ZID) in tablets in the presence of abacavir (IS) and to quantify drugs. The proposed UPLC strategies required no derivatization or pre‐treatment of the target drugs.